ANALISIS DASAR FILOSOFIS PERUBAHAN KURIKULUM 2013 - KURIKULUM MERDEKA - Sesrita, Afridha; Setiahati, Ignasius Putera; Amran; Sumatri, Mohamad Syarif; Utomo, Erry; Nurhasanah, Nina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Due to changing times, the curriculum must always change, from 2013 to Merdeka. The fundamental question is, what exactly is the basis of the change? Therefore, this article aims to determine what essentially underlies the change from the 2013 curriculum to the Merdeka curriculum. The method used is a descriptive qualitative method with literature analysis. This literature research found that the change occurred to answer the challenges of the existing era and the nature of education itself. The essence of education is to humanize humans, so with the Merdeka curriculum, humans are more human, not depressed, but can develop themselves optimally by being free. The Merdeka curriculum wants students to learn pleasantly rather than be depressed, and educators are expected to educate happily.